Análise direta de fertilizantes minerais empregando fluorescência de raios-X - Soares, Melissa Tomaz (Universidade Federal de São Carlos, 2022)
The present work aimed to theoretically evaluate the use of x-ray fluorescence in the direct analysis of mineral fertilizers, ensuring effectiveness and quality for the research and development sector, in the laboratory analysis of the development of new fertilizers. Fertilizers, in addition to playing a key role in crop production around the world, provide food, fodder, fiber, and even alternative fuel for the world's population. MAPA (Ministry of Agriculture, Livestock and Supply) regulates and guides regarding the techniques used for the analysis of raw materials and fertilizers in the agribusiness sector, even so, more and more, new analysis techniques have been developed, such as, the use of x-ray fluorescence. Among the advantages of its use, we highlight the ease of sample preparation, high resolution, multiple measurements of elements within the same sample, in addition to the non-destructive analysis. Therefore, despite the minority use of the XRF technique for fertilizer analysis, the technique proves to be effective and very advantageous, and its use in research centers related to the agricultural environment should be encouraged and explored more and more.
Direct analysis of mineral fertilizers by X-ray fluorescence spectrometry
Keywords: Agricultura; Produtividade; Fertilizantes; Nutrientes; Fluorescência de raios-x; CIENCIAS EXATAS E DA TERRA::QUIMICA